Aluminum material with surface covered with nanometer aluminum oxide layer and preparation method and application of aluminum material
By generating the method of generating nano-aluminum oxide layer on the surface of the metal aluminum, the problem of hydrogen analysis in the electrochemical synthesis of aluminum cathode is solved, and the high-efficiency 2-phenyl phenolic pheasant electrochemical hydrogen reduction reduction has been achieved. Rate.
Patent Information
- Application Number
- CN202411536338.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Metal aluminum is prone to hydrogen evolution reactions when used as a cathode, resulting in less application in electrochemical synthesis.
By placing metal aluminum tablets in hydrochloric acid for electrolytic oxidation, the aluminum material covered with aluminum layer covered by the surface is generated, and the porous three -dimensional mesh structure of the nano oxide layer and Louis acidity are used to suppress the hydrogen analysis.
The high-efficiency 2-phenyl phenolic electrochemical hydrogen hydrogenation of electrochemical synthesis was achieved, and the conversion rate, yield and Faraday efficiency reached more than 90%, avoiding the use of transition metal catalysts.
Smart Images

Figure CN119372738A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano metal oxide materials, and in particular is an aluminum material with a nano aluminum oxide layer on its surface, and a preparation method and application thereof. Background Art
[0002] The content of aluminum in the earth's crust ranks third only to oxygen and silicon, and it is the most abundant metal element in the earth's crust. Metal aluminum is a silvery-white light metal with ductility and an electrical conductivity of about 60% of copper. If measured by unit mass, the electrical conductivity of aluminum exceeds that of copper, and it often replaces copper in long-distance transmission. It is widely used for its lightness, good electrical and thermal conductivity, high reflectivity and oxidation resistance. Due to its good electrical conductivity, metal aluminum can be used as an electrode in electrochemical reactions, and is often used as an anode sacrificial electrode in electrochemical synthesis. Metal aluminum can also be used as a cathode, but due to its low overpotential, it is prone to hydrogen evolution reaction and is less used in electrochemical synthesis.
[0003] The oxidized aluminum can form an oxide film with a thickness of about 5 to 20 microns on the surface. It has high hardness, good heat resistance and insulation, and higher corrosion resistance than chemical oxide film. It is porous and has good adsorption capacity, but it loses conductivity and is not suitable for electrochemical reactions. The electron tunneling effect refers to the phenomenon that electrons travel from high potential areas to low potential areas and break through the classical forbidden area. When the thickness of the insulating layer is a few nanometers, a significant electron tunneling effect will occur, turning the material that should be an insulator into a conductor.
[0004] Based on the above research, the present invention provides an aluminum electrode material with a surface covered with nano-aluminum oxide, and a preparation method and application thereof. Summary of the invention
[0005] In view of the problem that metallic aluminum is less used in electrochemical synthesis because it is prone to hydrogen evolution reaction when used as a cathode, the present invention provides an aluminum material with a surface covered with nano-aluminum oxide and a preparation method and application thereof, thereby overcoming the type limitations and scarcity of applications of aluminum material electrodes in the prior art.
[0006] The present invention provides a method for preparing an aluminum material with a surface covered with a nano-aluminum oxide layer. The preparation method comprises placing a metal aluminum sheet with a polished surface in hydrochloric acid for electrolytic oxidation, washing and drying, and obtaining an aluminum electrode material with a surface covered with a nano-aluminum oxide layer, wherein the nano-aluminum oxide layer contains chlorine.
[0007] Furthermore, the metal aluminum sheet is made of pure aluminum with a purity of more than 99%.
[0008] Furthermore, the thickness of the metal aluminum sheet is greater than 0.5 mm.
[0009] Furthermore, the grinding method is grinding with sandpaper or grinding wheel.
[0010] Furthermore, the concentration of the hydrochloric acid is 1M-2M.
[0011] Furthermore, the electrolysis time is 1-2h, and the electrolysis current is 10mA-15mA.
[0012] Furthermore, the nano-aluminum oxide layer has a thickness of 2-4 nm and is a porous three-dimensional network structure.
[0013] The aluminum material prepared by the method of the present invention can be used as the cathode of the reaction electrode for the electrochemical hydrogenation reduction of 2-phenylthiophene. Specifically, the aluminum material with the surface covered with nano-aluminum oxide is used as the cathode, and 2-phenylthiophene is used as the raw material. The corresponding hydrogenation product 2-phenyltetrahydrothiophene is obtained by direct current electrolysis in an organic solvent. The conversion rate, yield and Faraday efficiency of the reaction can reach more than 90%. Since the use of transition metal catalysts is avoided, the disadvantage that sulfur-containing heterocycles are difficult to hydrogenate and catalyze is overcome, and the synthesis and preparation of saturated sulfur-containing compounds is realized. The activity of the nano-aluminum oxide layer catalyzing the electrochemical hydrogenation of 2-phenylthiophene within the preparation condition range of the present invention is basically the same.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] 1) The present invention uses pure aluminum as the aluminum material substrate, removes the aluminum oxide on the surface by grinding, and then places it in a hydrochloric acid solution of a certain concentration for electrolytic oxidation, and the nano aluminum oxide layer generated on the surface of the metal aluminum contains chlorine. The present invention uses hydrochloric acid as the electrolyte instead of the commonly used dilute sulfuric acid in industry, and can better control the morphology and thickness of the surface oxide film during the electrolysis process, and can introduce chlorine on the surface to obtain Lewis acid catalytic ability.
[0016] 2) The aluminum oxide generated on the surface of the aluminum material in the present invention is nanometer-level and has better conductivity than the traditional micrometer-level aluminum oxide.
[0017] 3) The nano-aluminum oxide layer generated on the surface of the aluminum material in the present invention has a porous three-dimensional network structure, has a large specific surface area, and has a good adsorption effect when used as an electrode.
[0018] 4) The nano-aluminum oxide layer on the surface of the aluminum material in the present invention has a strong ability to inhibit hydrogen evolution, and can effectively reduce the HER side reaction during the cathode reaction.
[0019] 5) The present invention combines the surface of the aluminum material to in-situ generate Lewis acid sites containing chloroaluminum bonds to achieve electrocatalytic ability.
[0020] 6) When the aluminum material with a surface covered with a nano-aluminum oxide layer prepared in the present invention is used as the cathode of the reaction electrode, it has a good effect on the electrochemical hydrogenation reduction of 2-phenylthiophene. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanning electron microscope (SEM) image of the chlorine-containing nano-aluminum oxide layer prepared in Example 1 of the present invention, wherein a) is 10 mm; b) is 1 mm.
[0022] Figure 2 The surface elements of the chlorine-containing nano-aluminum oxide layer prepared in Example 1 are characterized by scanning electron microscopy and X-ray energy dispersive spectroscopy (EDS-mapping), wherein a) is the full SEM image; b) is the X-ray energy dispersive spectrum-aluminum element; c) is the X-ray energy dispersive spectrum-oxygen element; d) is the X-ray energy dispersive spectrum-chlorine element;
[0023] Figure 3 The figures are comparison diagrams of X-ray diffraction spectra of different aluminum materials, where a) is 5052-Al; b) is the chlorine-containing nano-aluminum oxide layer prepared in Invention Example 1; and c) is metallic aluminum.
[0024] Figure 4 This is the XPS depth analysis spectrum of the aluminum material with surface covered with nano-aluminum oxide according to Example 1 of the present invention.
[0025] Figure 5 The following are comparison charts of interface resistance tests of different aluminum-based materials, where a) is the surface of chlorine-containing nano-aluminum oxide layer; b) is polished metal aluminum; c) is 5052-Al.
[0026] Figure 6 The linear sweep voltammogram and Tafel slope diagram of the aluminum material with surface covered with nano-alumina prepared in Example 1 and the polished metal aluminum in Comparative Example 1 are compared, wherein a) is the linear sweep voltammogram; b) is the Tafel slope diagram;
[0027] Figure 7 The bar graphs are of the conversion rate, yield and Faraday efficiency of the electrocatalytic hydrogenation of 2-phenylthiophene in Example 1 of the present invention and Comparative Example 1, wherein a) the cathode is an aluminum material covered with a nano-chlorine-containing aluminum oxide layer; and b) the cathode is polished metallic aluminum. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with specific embodiments. The following embodiments are only used to illustrate the present invention and should not be construed as limiting the present invention itself. Various changes can be made to the present invention in form and detail without departing from the spirit and scope of the present invention.
[0029] Materials involved in the examples and comparative examples: 99% pure aluminum and hydrochloric acid were obtained from Sinopharm Group, where the thickness of aluminum was 0.8 mm, and 2-phenylthiophene was obtained from Adamas with a purity of 99%. It should be noted that materials and reagents from other suppliers have the same effect as long as their purity is similar. The aluminum material covered with micron-grade aluminum oxide, i.e., 5052-Al, was obtained from Sinopharm Group, and the thickness of the aluminum oxide film on the surface was 3 microns.
[0030] Example 1
[0031] 1) This embodiment provides a method for preparing an aluminum material with a surface covered with a nano-aluminum oxide layer, and the steps are as follows: cut a pure aluminum sheet (metal aluminum with a purity of 99%) with a specification of 1.5cm*1cm*0.8mm, and carefully polish its surface with sandpaper, with a polishing area of 1cm*1cm. Then fix it with an electrode clamp, and perform oxidation electrolysis in 1M dilute hydrochloric acid. The anode is a polished aluminum sheet, the cathode is a graphite felt (immersed in the solution 1cm*1cm*2mm), the current is 10mA, and the electrolysis time is 2h. After the electrolysis is completed, the obtained aluminum material is washed with deionized water, and then ultrasonically cleaned in deionized water for 3min to clean the surface (remove the hydrochloric acid that may remain on the surface and a small amount of granular aluminum and aluminum oxide and other substances), and then blown dry with nitrogen. The obtained material is an aluminum material with a surface covered with nano-aluminum oxide.
[0032] 2) The prepared aluminum material is subjected to an electrical reaction according to the following method:
[0033] Tetraethylammonium chloride (67.0 mg, 0.4 mmol) and 2-phenylthiophene (32 mg, 0.2 mmol) were added to a transparent three-necked reaction bottle with a volume of 10 mL. The left and right bottle openings were plugged with rubber stoppers equipped with an anode (graphite felt, immersion volume 1 cm*1 cm*2 mm) and a cathode (aluminum material with nano-alumina surface covered as prepared in the example, immersion area 1 cm*1 cm). 5 mL of N,N-dimethylformamide was added from the middle bottle opening, and then 100 μL of ethanol was used as a microinjector to purge with ammonia. After exhausting the air in the reaction bottle, a rubber stopper was plugged in the middle bottle opening and an ammonia balloon was inserted. The reaction bottle was placed on a magnetic stirrer, connected to electrodes, and the current was set to 10 mA. The reaction was stirred at this current for 2.14 hours. After the reaction was completed, the reaction product was extracted with ethyl acetate, the organic phase was washed with saturated brine, dried over anhydrous sodium sulfate, filtered, and the filtrate was spin-dried. Column chromatography technology was used with 300-400 mesh silica gel as the stationary phase, dry loading, elution was performed with petroleum ether as the eluent, the eluate was detected by GC-MS, and the collected chromatographic liquid was concentrated to obtain 29.5 mg of the product 2-phenyltetrahydrothiophene.
[0034] Example 2
[0035] The electrode material preparation steps and the electrical reaction steps were the same as those in Example 1, except that 2-phenylthiophene (32 mg, 0.2 mmol) was replaced with 2-p-tolylthiophene (34.8 mg, 0.2 mmol). Finally, 28.5 mg of the product 2-p-tolyltetrahydrothiophene was obtained.
[0036] Example 3
[0037] The electrode material preparation steps and the electrical reaction steps were the same as those in Example 1, except that 2-phenylthiophene (32 mg, 0.2 mmol) was replaced with 2-p-fluorophenylthiophene (35.6 mg, 0.2 mmol). Finally, 29.5 mg of the product 2-p-fluorophenyltetrahydrothiophene was obtained.
[0038] Example 4
[0039] The electrode material preparation steps and the electroreaction steps were the same as those in Example 1, except that 2-phenylthiophene (32 mg, 0.2 mmol) was replaced with biphenyl (30.8 mg, 0.2 mmol), the electrolysis time was 4 hours, and the electrolysis current was 12.5 mA. Finally, 19.2 mg of cyclohexylbenzene was obtained.
[0040] Comparative Example 1
[0041] The electrochemical reaction was carried out using polished aluminum as the cathode material, and the electrochemical reaction steps were the same as those in Example 1. Finally, 12.7 mg of the product 2-phenyltetrahydrothiophene was obtained.
[0042] Comparative Example 2
[0043] An aluminum material with a surface covered with a nano-aluminum oxide layer (wherein the hydrochloric acid concentration is 12M) was used for the electroreaction, and the electroreaction steps were the same as those in Example 1. Finally, 13.7 mg of the product 2-phenyltetrahydrothiophene was obtained.
[0044] Comparative Example 3
[0045] An aluminum material with a surface covered with a nano-aluminum oxide layer (the electrolysis time of the prepared material is 4 hours) was used for the electroreaction, and the electroreaction steps were the same as those in Example 1. Finally, 14.3 mg of the product 2-phenyltetrahydrothiophene was obtained.
[0046] The surface of the aluminum material covered with nano-alumina prepared in Example 1 has a SEM ( Figure 1 ) shows that the surface morphology of the aluminum material covered with nano-alumina is a porous three-dimensional network structure. Figure 2) shows that the nano-aluminum oxide layer covering the surface of the material contains chlorine, oxygen and aluminum elements, that is, the nano-aluminum oxide covering the surface of the aluminum material is a layer of chlorine-containing aluminum oxide. X-ray diffraction spectrum ( Figure 3 ) shows that the surface element composition of the aluminum material covered with nano-alumina prepared in Example 1 is similar to that of aluminum oxide, which is significantly different from metallic aluminum.
[0047] Figure 4 The XPS depth analysis spectrum (0-10 nm) of the aluminum material with the surface covered with nano-aluminum oxide prepared in Example 1 of the present invention, and the X-ray photoelectron etching spectrum can test the thickness of the nano layer. The analysis shows that the thickness of the chlorine-containing aluminum oxide layer is 2-4 nanometers.
[0048] Figure 5 This is a resistance test comparison chart of the aluminum material with nano-alumina on the surface prepared in Example 1, the polished metal aluminum in Comparative Example 1, and the aluminum material with micron-grade alumina on the surface; Figure 5 It can be seen that the aluminum material with the surface covered with nano-aluminum oxide in Example 1 of the present invention has a resistance much greater than that of metal aluminum and micron-sized aluminum oxide, and also has good conductivity.
[0049] Figure 6 The linear sweep voltammogram and Tafel slope diagram of the aluminum material with nano-alumina on the surface prepared in Example 1 and the polished metal aluminum in Comparative Example 1 are compared. Figure 6 It can be seen that compared with polished metallic aluminum, the aluminum material covered with a nano-aluminum oxide layer has a higher hydrogen evolution reaction reduction and a larger Tafel slope, which proves that the aluminum material covered with a nano-aluminum oxide layer has a good inhibitory effect on the hydrogen evolution reaction (HER).
[0050] Figure 7 This is a bar chart comparing the electrocatalytic hydrogenation performance of 2-phenylthiophene of Example 1 and Comparative Example 1 of the present invention. The electrochemical reduction performance results of Example 1 and Comparative Examples 1 to 3 are shown in Table 1:
[0051] Table 1
[0052] Cathode material Conversion rate Yield Faraday efficiency Example 1 95% 90% 90% Comparative Example 1 45% 39% 39% Comparative Example 2 49% 42% 42% Comparative Example 3 51% 44% 44%
[0053] As shown in Table 1, the conversion rate, yield and Faraday efficiency of the reaction when using aluminum materials covered with nano-alumina on the surface are more than twice as high as those when using polished metal aluminum. Compared with polished metal aluminum, aluminum materials covered with nano-alumina layers on the surface have larger specific surface area, higher Tafel slope and stronger Lewis acidity, which are beneficial to the electron reduction process of 2-phenylthiophene on the electrode surface, so that the reaction can obtain the corresponding product with a conversion rate of 95%, a yield of 90% and a Faraday efficiency, which is much better than the polished metal aluminum electrode. Changing the electrolysis current and the concentration of hydrochloric acid used for electrolysis will make the effect of the material worse.
[0054] Table 2 shows that the use of aluminum materials with surface covered nano-alumina has a good effect on the conversion of various thiophene compounds. At the same time, this material can also be used for the reduction and hydrogenation of biphenyl.
[0055] Table 2
[0056] Cathode material Yield Faraday efficiency Example 1 90% 90% Example 2 81% 81% Example 3 80% 80% Example 4 60% 45%
[0057] The molecular structural formula of the product 2-phenyltetrahydrothiophene in Example 1 is as follows:
[0058]
[0059] Example 1 Product 2-phenyltetrahydrothiophene NMR spectrum: 1 H NMR (400MHz, Chloroform-d) δ7.44 (d, J=7.4Hz, 2H), 7.33 (t, J=7.5Hz, 2H), 7.25 (t, J=7.3Hz, 1H), 4.61-4. 49(m, 1H), 3.14~3.25(m, 1H), 3.02-3.07(m, 1H), 2.39-2.44(m, 1H), 2.27-2.34(m, 1H), 2.16-1.92(m, 2H). 13 CNMR (101MHz, CDCl3) δ143.0, 128.4, 127.6, 126.9, 52.7, 40.5, 33.4, 31.0.
[0060] The molecular structural formula of the product 2-p-tolyltetrahydrothiophene of Example 2 is as follows:
[0061]
[0062] Example 2 The product 2-p-tolyltetrahydrothiophene NMR spectrum: 1H NMR (400MHz, Chloroform-d) δ7.34 (d, J=8.1Hz, 2H), 7.15 (d, J=7.8Hz, 2H), 4.71-4.41 (m, 1H), 3.22-3 .14(m, 1H), 3.07-3.01(m, 1H), 2.46-2.38(m, 1H), 2.36(s, 3H), 2.34-2.27(m, 1H), 2.11-1.91(m, 2H). 13 C NMR (101 MHz, CDCl 3 )δ139.9, 136.6, 129.1, 127.5, 52.5, 40.5, 33.4, 31.0, 21.0.
[0063] The molecular structural formula of the product 2-p-fluorophenyltetrahydrothiophene of Example 3 is as follows:
[0064]
[0065] Example 3 Product 2-p-Fluorophenyltetrahydrothiophene NMR spectrum: 1 H NMR(400MHz,Chloroform-d)δ7.45–7.35(m,2H),7.03–6.98(m,2H),4.57–4.48(m,1H),3.2 1–3.13(m,1H),3.07–3.00(m,1H),2.44–2.36(m,1H),2.32–2.24(m,1H),2.08–1.86(m,2H). 13 C NMR (101MHz, Chloroform-d) δ 161.8 (d, J = 245.1Hz), 138.7 (d, J = 3.1Hz), 129.1 (d, J = 7.9Hz), 115.1 (d, J = 21.3Hz), 52.0, 40.7, 33.4, 30.9.
[0066] The molecular structural formula of the product cyclohexylbenzene of Example 4 is as follows:
[0067]
[0068] Example 4: Cyclohexylbenzene NMR spectrum: 1 H NMR (400MHz, Chloroform-d) δ7.37–7.30(m,2H),7.29–7.18(m,3H),2.63–2.48(m,1H),1.98–1.75(m,5H),1.53–1.38(m,4H),1.36–1.23(m,1H). 13 C NMR (101 MHz, CDCl3 )δ148.1,128.3,126.8,125.8,44.6,34.5,26.9,26.2.
Claims
1. A method for preparing an aluminum material having a surface covered with a nano-aluminum oxide layer, characterized in that: The polished aluminum sheet is placed in hydrochloric acid for electrolytic oxidation, cleaned and dried to obtain an aluminum electrode material covered with a nano aluminum oxide layer, wherein the nano aluminum oxide layer contains chlorine.
2. The preparation method according to claim 1, characterized in that: The metal aluminum sheet is made of pure aluminum with a purity of more than 99%.
3. The preparation method according to claim 1, characterized in that: The thickness of the metal aluminum sheet is greater than 0.5 mm.
4. The preparation method according to claim 1, characterized in that: The grinding method is grinding with sandpaper or grinding wheel.
5. The preparation method according to claim 1, characterized in that: The concentration of the hydrochloric acid is 1M-2M.
6. The preparation method according to claim 1, characterized in that: The electrolysis time is 1-2h, and the electrolysis current is 10mA-15mA.
7. The preparation method according to claim 1, characterized in that: The thickness of the nano aluminum oxide layer is 2-4 nm, and it is a porous three-dimensional network structure.
8. An aluminum material prepared by the preparation method according to any one of claims 1 to 7.
9. The aluminum material according to claim 8, characterized in that: The aluminum electrode material is used to prepare the cathode of the reaction electrode.
10. Use of the aluminum electrode material according to claim 9 in the electrochemical hydrogenation reduction of 2-phenylthiophene.
Citation Information
Patent Citations
Method for forming nanoscale porous membrane layer on pure aluminum surface
CN103276438A
Method for preparing CoMo-family hydrogenation desulfurization catalyst by vapor deposition
CN110252321A
Production of free superthin porous alumina template with controllable thickness
CN1712574A
Preparation process of metal aluminium template for assembling nano-micron array material
CN1807701A
Electrochemical method of producing aluminium oxide
RU2412904C1